Giant mucinous cystadenoma: a case report - Gwanzura, Chipo (J Med Case Rep, 2019)
INTRODUCTION: Giant ovarian cysts are rarely described in the literature, owing to the availability of advanced imaging technologies in developed countries leading to early treatment. In resource-limited settings, various factors lead to late presentation. CASE PRESENTATION: We present a case of a 48-year-old black African woman with a giant mucinous cystadenoma who presented to a tertiary hospital with massive abdominal distention 5 years after being referred from a district hospital for the same problem. Surgical management resulted in fatal complications. CONCLUSIONS: The surgical management of these huge tumors is associated with many life-threatening complications. Transvaginal ultrasound should be used in resource-limited settings to delineate ovarian masses. Community health workers must be involved in scouting and follow up of community members with unusual abdominal swellings in developing countries to avoid delays in care.